1991
DOI: 10.1002/ijc.2910470113
|View full text |Cite
|
Sign up to set email alerts
|

Heterotransplantation of human breast carcinomas in nude mice. Correlation between successful heterotransplants, poor prognosis and amplification of the her‐2/neu oncogene

Abstract: Four hundred and thirty-three human breast carcinomas and 23 cell lines derived from human breast carcinomas were heterotransplanted in nude mice. Twenty-eight tumors and 13 cell lines took and could be serially transplanted. Their human origin was established by isozyme analysis performed on successive passages. Sixteen primary infiltrating duct-cell carcinomas (PIDC) took, from a total of 262 transplanted (6.1%). This is in striking contrast to the greater than 50% rate of takes of most major cancers of epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 20 publications
3
24
0
Order By: Relevance
“…However, the technical problems have prevented a more widespread usage of this system for studying primary breast cells from surgical specimens. The transplantation take of 262 surgical breast specimens, by far the largest number in a single study, has been reported to be only 6% (Giovanella et al 1991), although a much higher take can be accomplished by co-injection with fibroblasts (Romijn 1991), collagen gel (Yang et al 1994, or Matrigel (Fridman et al 1991, Mehta et al 1993. Transplantation of non-malignant breast tissues into nude mice has also been reported (Jensen & Wellings 1976, Gusterson et al 1984, McManus & Welsch 1984.…”
Section: Discussionmentioning
confidence: 99%
“…However, the technical problems have prevented a more widespread usage of this system for studying primary breast cells from surgical specimens. The transplantation take of 262 surgical breast specimens, by far the largest number in a single study, has been reported to be only 6% (Giovanella et al 1991), although a much higher take can be accomplished by co-injection with fibroblasts (Romijn 1991), collagen gel (Yang et al 1994, or Matrigel (Fridman et al 1991, Mehta et al 1993. Transplantation of non-malignant breast tissues into nude mice has also been reported (Jensen & Wellings 1976, Gusterson et al 1984, McManus & Welsch 1984.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of the erbB-2 tyrosine kinase receptor has been shown to be a key determinant in neoplastic transformation and progression in a variety of neoplasms including epithelial malignancies of the breast, lung, stomach, and ovary (24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…A drawback of this assay, at least in its current form, is that it would not distinguish between progenitor cells that have the ability to generate an outgrowth composed solely of terminally differentiated cells versus cells that have the ability to generate outgrowths that contain primitive progenitor cells in addition to terminally differentiated cells. Another potential drawback to this assay is the observation that human breast tumours have a very low engraftment success rate when xenotransplanted subcutaneously or into the fat pads of immune-deficient mice [49][50][51][52][53], For example, in one study where 433 primary human mammary carcinomas were implanted into nude mice, only 28 (6.1%) of the xenotransplants generated successful outgrowths [53]. The highest reported rates of engraftment (>90%) of human tumour fragments into immune-deficient mice have been observed when the tissue is transplanted to highly vascular sites, such as under the renal capsule or intramuscularly [54][55][56].…”
Section: In Vivo Models To Detect Human Mascsmentioning
confidence: 99%